Pembuatan Hand Sanitizer Non-Alkohol dari Ekstrak Daun Sirih sebagai Solusi Adanya Sensivitas Kulit terhadap Alkohol - Putri Arisa; Nurhayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract: Corona virus is a new type of virus that can cause symptoms such as MERS-CoV and SARS-CoV. Covid-19 transmission can occur through a splash from the mouth or nose of an infected person with Covid-19. The risk of covid-19 transmission is increasing and the public is required to be ready to stop the spread and transmission of covid-19. The existence of prevention to prevent the increase of the corona virus is very necessary, one of which is the use of hand sanitizers as a public health protocol. This study used the main ingredients of betel leaf and lime leaf extracts. Betel leaf contains saponins, flavonoids, polyphenols and essential oils which function as antimicrobials. Hand sanitizer made from betel leaf and lime leaf extract is a relatively safe hand sanitizer and can be used as a solution for people who are sensitive to alcohol. Making hand sanitizers using natural ingredients, namely betel and lime leaf extracts is very practical and does not cost a fortune. 15% betel leaf extract is as effective as alcohol. Keywords: Covid-19; Hand Sanitizer; Betel leaf; Lime